2005
DOI: 10.1111/j.1399-302x.2005.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of mutans streptococci by intact cell matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry

Abstract: It is difficult to distinguish mutans streptococci on the species level, and even more so on the subspecies level. Intact cell matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) (ICM) was applied to reference strains of five of the species of the mutans group (Streptococcus criceti, Streptococcus downei, Streptococcus mutans, Streptococcus ratti, Streptococcus sobrinus), nonmutans streptococci (Streptococcus oralis, Streptococcus mitis, Streptococcus salivarius, and Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
1
39
0
2
Order By: Relevance
“…Furthermore, it has been reported that S. criceti strains AHT and E49 should be reclassified as S. ratti strains (27). Although some strains of S. criceti used by researchers have been reclassified, it is probable that our reference strain, S. criceti E49, is S. criceti (serotype a) because of the identical nucleotide sequence of the dex gene to that of S. criceti ATCC19642 (type strain).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that S. criceti strains AHT and E49 should be reclassified as S. ratti strains (27). Although some strains of S. criceti used by researchers have been reclassified, it is probable that our reference strain, S. criceti E49, is S. criceti (serotype a) because of the identical nucleotide sequence of the dex gene to that of S. criceti ATCC19642 (type strain).…”
Section: Discussionmentioning
confidence: 99%
“…Special emphasis was laid on the correct species identification of the streptococci. As it is known that conventional biochemical tests may fail to discern certain species of viridans streptococci, the recently established MALDI-TOF-MS methodology (Smole et al, 2002;Rupf et al, 2005;Friedrichs et al, 2007) was used and adjusted for this study.…”
Section: Resultsmentioning
confidence: 99%
“…Special emphasis was laid on the correct species identification of the streptococci. As it is known that conventional biochemical tests may fail to discern certain species of viridans streptococci, the recently established MALDI-TOF-MS methodology (Smole et al, 2002;Rupf et al, 2005;Friedrichs et al, 2007) was used and adjusted for this study.The results indicated that, among the 11 species cultured from patients and healthy individuals, only one species -S. sanguinis -showed significant differences in colonization rates for the two groups, and was associated with health rather than disease.It has been demonstrated previously that S. sanguinis is a beneficial bacterium in the prevention of dental caries. The antagonism with S. mutans has been known for many years.…”
mentioning
confidence: 99%
“…A publication in 2000 suggested that mass spectra of spore cells of the Bacillus cereus group allow differentiation from other Bacillus species (17), streptococci of the mutans group were successfully differentiated by MALDI-TOF MS in 2005 (16), and viridians streptococci have been successfully discriminated by MALDI-TOF MS in 2007 (9). By now, dedicated mass spectrometry systems are established for routine species identification in many laboratories that achieve discrimination of even closely related species by the comparison of spectrum fingerprints acquired within minutes from tiny amounts of colony material to exhaustive reference databases.…”
Section: Discussionmentioning
confidence: 99%